2013
DOI: 10.2174/1874336601306010001
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Trauma Reduces the Impact of Batrachochytrium dendrobatidis in Fowler's Toads (Anaxyrus fowleri)

Abstract: The amphibian epidermis presents many barriers that prevent pathogen infection. Much effort has been placed on examining determinants of infectivity and pathogenicity of Batrachochytrium dendrobatidis (Bd) in amphibians. However, no research has examined how trauma to the epidermis can affect susceptibility to and virulence of Bd infections in amphibians. Trauma is a common entry point for secondary infections that would otherwise be immunologically defensible to a host. The objective of our study was to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The detected late gene activation of these downstream signaling pathways may alternatively be associated with cellular stress and trauma or secondary bacterial infections ( 151 ), producing damage associated molecular patterns (DAMPs) that are similarly recognized by PRRs and protease-activated receptors (PARs) ( 154 ). These findings are consistent with the results of Brem and Parris ( 155 ) who showed that toads were less likely to be become infected if the epidermis was scraped (causing erosions) prior to Bd exposure. Priming of the innate immune system in response to trauma (Bd-associated epidermal erosions) may contribute to amplification of the innate response, leading to an exacerbated late-stage response.…”
Section: Innate Immune Defensessupporting
confidence: 92%
See 1 more Smart Citation
“…The detected late gene activation of these downstream signaling pathways may alternatively be associated with cellular stress and trauma or secondary bacterial infections ( 151 ), producing damage associated molecular patterns (DAMPs) that are similarly recognized by PRRs and protease-activated receptors (PARs) ( 154 ). These findings are consistent with the results of Brem and Parris ( 155 ) who showed that toads were less likely to be become infected if the epidermis was scraped (causing erosions) prior to Bd exposure. Priming of the innate immune system in response to trauma (Bd-associated epidermal erosions) may contribute to amplification of the innate response, leading to an exacerbated late-stage response.…”
Section: Innate Immune Defensessupporting
confidence: 92%
“…However, a study in B. boreas by Murphy et al ( 181 ) found that previously exposed frogs survived slightly longer if they had a dry habitat option upon re-exposure. A study by McMahon et al ( 182 ) found that multiple prior exposures to Bd slowed the rate of progression of chytridiomycosis, although this finding may instead be associated with repeated innate immune priming through trauma ( 155 ). The variable results of these studies may be associated with differing routes of immunization or dose-rates of Bd exposure.…”
Section: Adaptive Immune Responsementioning
confidence: 99%
“…Batrachochytrium dendrobatidis culture was prepared using a strain (FMB 003 [ 51 ];) isolated from a local, infected L. sphenocephalus adult in 2010 at Meeman-Shelby State Park, Shelby County, Tennessee, USA. Plates were prepared on 1% tryptone agar from 2 ml of homogenized Bd stock culture, sealed, and incubated at room temperature for 10 d. Following incubation, plates were flooded with 3 ml of aged tap water for 45 min to harvest zoospores.…”
Section: Methodsmentioning
confidence: 99%
“…Nor does the presence of constitutive resistance result in immunological memory post-infection (i.e. infections have no lasting protective effect on subsequent exposures, although consider innate immune memory; [ 59 , 60 ]). Thus, infections can become persistent often with increasing pathogen burden trajectories and can result in mortality if pathogen optimal environmental conditions are maintained.…”
Section: Why Do Infection Tolerance and Resistance Matter In Chytridi...mentioning
confidence: 99%